The role of computer literacy on employee performance in the hotel industry - LUGAIRE ERIMIYA (Uganda Christian University, 2024)
This study investigates the role of computer literacy on employee performance in the hotel industry. With the ongoing transformation in hospitality, the ability of employees to effectively use computers has become essential for achieving operational excelence and enhancing guest experience.